2021
DOI: 10.1039/d1ma00468a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of a hydrophilic MIL-160-based membrane demonstrate pressure-dependent selective uptake of industrially relevant greenhouse gases

Abstract: The continued integration of technology capable of achieving higher degrees of sustainability while meeting global material and energy demands is of singular importance in halting human-caused climate change. Unit operations...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…[102] It was also demonstrated by Chapman et al, using molecular dynamics simulations, that a MIL-160-based membrane demonstrated pressure-dependent selective uptake of CO 2 in the presence of other gas species, such as CH 4 , NO 2 , and NO. [106] Similar molecular simulation studies have also shown that MIL-160 has an outstanding SO 2 /CO 2 selectivity, up to 220 times more selective for SO 2 (298 K, 1 bar), which is attributed to the furanyl group's SO 2 binding affinity. [100] More recently, Fan et al were able to experimentally demonstrate that a MIL-160/CAU-10-F mixed ligand MOF membrane has excellent CO 2 /CH 4 separation capabilities.…”
Section: Metal-organic Frameworkmentioning
confidence: 61%
See 3 more Smart Citations
“…[102] It was also demonstrated by Chapman et al, using molecular dynamics simulations, that a MIL-160-based membrane demonstrated pressure-dependent selective uptake of CO 2 in the presence of other gas species, such as CH 4 , NO 2 , and NO. [106] Similar molecular simulation studies have also shown that MIL-160 has an outstanding SO 2 /CO 2 selectivity, up to 220 times more selective for SO 2 (298 K, 1 bar), which is attributed to the furanyl group's SO 2 binding affinity. [100] More recently, Fan et al were able to experimentally demonstrate that a MIL-160/CAU-10-F mixed ligand MOF membrane has excellent CO 2 /CH 4 separation capabilities.…”
Section: Metal-organic Frameworkmentioning
confidence: 61%
“…It has been predicted in silico that at high pressure, the 3D structure of MIL‐160 induces a more efficient packing of CO 2 over the other gases, and as such, presents an avenue for CO 2 recovery from N 2 , CO, and CH 4 [102] . It was also demonstrated by Chapman et al., using molecular dynamics simulations, that a MIL‐160‐based membrane demonstrated pressure‐dependent selective uptake of CO 2 in the presence of other gas species, such as CH 4 , NO 2 , and NO [106] . Similar molecular simulation studies have also shown that MIL‐160 has an outstanding SO 2 /CO 2 selectivity, up to 220 times more selective for SO 2 (298 K, 1 bar), which is attributed to the furanyl group's SO 2 binding affinity [100] .…”
Section: Hmf‐derived Nanomaterialsmentioning
confidence: 91%
See 2 more Smart Citations
“…We have chosen to study CA due to its direct applicability in the benign hydration of CO 2 , that can be combined synergistically with the selective CO 2 uptake of MIL-160 over a wide range of operating pressures . Complementarily, MPO was chosen for its integral role in the human immune response that endows it with the potential to be integrated in biomedical applications from surface decontamination to the detection of inflammation within the human body. , MIL-160 and ZIF-8 were selected as models for hydrophilic and hydrophobic MOF hybrids to be used for the sorption-based separation of greenhouse gases or size-exclusionary separation for the production of value-added chemicals through catalytic transformations, respectively.…”
Section: Resultsmentioning
confidence: 99%